A Preliminary Study of Molluscan Fauna of Singhori Wildlife Sanctuary, Raisen, Madhya Pradesh, India - Patil, Sachin R. (Indian Forester, 2013)
A consolidated list of freshwater and land molluscan species reported for the first time from the Singhori Wildlife Sanctuary, Raisen district of Madhya Pradesh. Overall 17 species of freshwater and land mollusca belonging to 11 genera, under 8 families and 4 orders are identified after studying 386 specimens. Habitat structure study indicates more species diversity in littoral zone inhabiting freshwater mollusca than benthic zone and land inhabitants.